2016
DOI: 10.1093/jxb/erw265
|View full text |Cite|
|
Sign up to set email alerts
|

Fine tuning chloroplast movements through physical interactions between phototropins

Abstract: HighlightPhysical interactions between phototropin molecules can alter their signaling outcomes, providing the means for the plant to fine-tune its blue light responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 52 publications
(105 reference statements)
5
40
0
Order By: Relevance
“…7). Partial defect in the avoidance response in the phot1 mutant was reported also in other studies (Luesse et al, 2010;Sztatelman et al, 2016). No detectable light-induced changes in leaf transmittance were observed in the phot1phot2 mutants ( Fig.…”
Section: Chloroplast Outer Membrane-associated Phot2 Induced the Chlosupporting
confidence: 86%
“…7). Partial defect in the avoidance response in the phot1 mutant was reported also in other studies (Luesse et al, 2010;Sztatelman et al, 2016). No detectable light-induced changes in leaf transmittance were observed in the phot1phot2 mutants ( Fig.…”
Section: Chloroplast Outer Membrane-associated Phot2 Induced the Chlosupporting
confidence: 86%
“…Previous studies revealed that the transitional light intensity in the Atphot1 mutant is similar to that in WT plants, suggesting that Atphot2 mainly controls the transitional light intensity in A. thaliana [31,32]. In addition, the transitional light intensity between the accumulation and avoidance responses is lowered by an engineered Atphot2 with a long-lifetime of the photoactivated state [33].…”
Section: Plos Onementioning
confidence: 89%
“…Notably, cold treatment had a more significant effect on the decrease of Atphot1 levels than the increase of Atphot2 levels [16], implying that the expression of Atphot1 might be more sensitive to cold than that of Atphot2. Previous studies indicated that Atphot1 and Atphot2 have the high and low activities, respectively, to induce the accumulation response in A. thaliana [31,32]. In this context, the cold-induced decrease of Atphot1 levels may contribute rapid physiological change from the accumulation response to cold-avoidance response in A. thaliana.…”
Section: Alteration Of Phot Expression Is Not Required For Induction mentioning
confidence: 95%
“…An attempt was made to compare the BrachPHOT1 and BrachPHOT2 mRNA levels with the protein levels evaluated by western blot. We used antibodies for Arabidopsis Anti-PHOT1 (AS10 720) and anti-PHOT2 (AS10 721) purchased from (Agrisera), detailed information in Łabuz et al ( 2015 ) and Sztatelman et al ( 2016 ). The experiment was repeated several times.…”
Section: Methodsmentioning
confidence: 99%